MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN BUDAYA MINAT BACA AL-QUR’AN DI MADRASAH ALIYAH SWASTA AINUL YAQIN KOTA JAMBI - Rahimah, Rahimah; Sumirah, Sumirah; Purnama, Boby Yasman (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the management of the madrasah principal in improving the culture of interest in reading the Qur'an at Madrasah Aliyah Swasta Ainul Yaqin, Jambi City, including the supporting factors, inhibiting factors, and the solutions implemented. This study uses a qualitative approach with a descriptive method through observation, interviews, and documentation, with research subjects consisting of the madrasah principal, teachers, and students. The results of the study indicate that the management of the madrasah principal is carried out through planning, organizing, implementing, and supervising, which are realized in regular tadarus programs and the habituation of reading the Qur'an before learning activities. Supporting factors include teacher commitment, foundation support, and a religious environment, while inhibiting factors include limited human resources and lack of teacher understanding. The solutions implemented include training, guidance, and collaboration with religious institutions, so that it can improve the culture of interest in reading the Qur'an and shape the religious character of students.